Kikuchi-Fujimoto Disease Associated with Myasthenia Gravis: A Case Report - Onasanya, Olukayode (Hindawi Publishing Corporation, 2010)
Kikuchi-Fujimoto disease is a self-limited benign condition of unknown etiology characterized by cervical lymphadenopathy, fever, and leucopenia. An autoimmune hypothesis has been suggested and an association with systemic lupus erythematosus, Sjogren's disease, and antiphospholipid syndrome has been noted. We report a 27-year-old male who presented for evaluation of weakness and he was diagnosed with seropositive generalized myasthenia gravis and underwent a thymectomy. He was stable until five months post-thymectomy, when he developed a high fever associated with nontender cervical lymphadenopathy, chills, and night sweats. Histopathology of a cervical lymph gland biopsy was compatible with Kikuchi-Fujimoto lymphadenitis. He improved spontaneously and was asymptomatic at the followup six months later. Our case expands the association of Kikuchi-Fujimoto disease with autoimmune disorders to include myasthenia gravis.